2014
DOI: 10.1007/s00403-014-1486-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Th17 cytokines in leprosy: correlation with circulating CD4+ CD25highFoxP3+ T-regs cells, as well as down regulatory cytokines

Abstract: Leprosy is not only a bacteriological disease but also an immunological disease, in which T helper17 and CD4(+) CD25(high)FoxP3(+) regulatory T cells (T-regs), among others, may play a role. We aimed to evaluate serum levels of interleukin (IL)-17, IL-22 (Th17 cytokines), IL-10 and transforming growth factor (TGF)-β (down regulatory cytokines) in 43 untreated leprosy patients and 40 controls by enzyme-linked immunosorbent assay, and to assess circulating CD4(+) CD25(high)FoxP3(+)T-regs in patients using flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
3
33
0
1
Order By: Relevance
“…Since T1R and T2R are both acute inflammation reactions, it is reasonable to discover a higher frequency of Th17 in both T1R and T2R compared to non-reactional leprosy considering the inflammation functions of Th17 cells (73)(74)(75). Comparing to other forms of leprosy and healthy controls, T2R showed lowest circulating Treg frequency, which was consistent with the high Th17 frequency in T2R (58,76). But it is not the case for T1R, several studies have demonstrated that T1R showed a significantly higher frequency of Treg compared to nonreactional leprosy in both PBMC and skin lesions (58,74,(76)(77)(78).…”
Section: The Reciprocal Relationship Between Regulatory T Cells and Tsupporting
confidence: 65%
“…Since T1R and T2R are both acute inflammation reactions, it is reasonable to discover a higher frequency of Th17 in both T1R and T2R compared to non-reactional leprosy considering the inflammation functions of Th17 cells (73)(74)(75). Comparing to other forms of leprosy and healthy controls, T2R showed lowest circulating Treg frequency, which was consistent with the high Th17 frequency in T2R (58,76). But it is not the case for T1R, several studies have demonstrated that T1R showed a significantly higher frequency of Treg compared to nonreactional leprosy in both PBMC and skin lesions (58,74,(76)(77)(78).…”
Section: The Reciprocal Relationship Between Regulatory T Cells and Tsupporting
confidence: 65%
“…These data are unprecedented and suggest that this population is related to a protective immunological activity against infection, contributing to the development of PB forms of the disease. Activation of these cells at the beginning of the contact with the M. leprae would lead to better control of bacillary load and attenuation of inflammatory injury . Recently, higher IL‐17 levels in supernatants of PBMC stimulated by M. leprae sonicated antigen of healthy contacts and tuberculoid form were related when compared to lepromatous form …”
Section: Discussionmentioning
confidence: 99%
“…Activation of these cells at the beginning of the contact with the M. leprae would lead to better control of bacillary load and attenuation of inflammatory injury. 21 Recently, higher IL-17 levels in supernatants of PBMC stimulated by M. leprae sonicated antigen of healthy contacts and tuberculoid form were related when compared to lepromatous form. 22 Household contacts feature a greater number of T H 17 cells: in Brazil, for operational purposes a household contact is considered any person who resides or has resided with the Hansen's disease patient in the last 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas STAT3 expression, an essential factor in the differentiation of Th17 cells, remains similar between patients with LL and TL, phosphorylated STAT3 is found at higher levels in patients with TL compared with patients with LL [60]. Simply put, severe forms of leprosy are associated with defective levels of IL-17 and an overproduction of the factors that lead to the differentiation of T regs [61]. The distinct role of IL-17 in cancer, however, seems less certain, as recent studies have demonstrated the plasticity of this T cell subset with heterogeneous functions that may be tissue specific [62].…”
Section: Th17 and T Regsmentioning
confidence: 99%